Improving the transport classification of goods for plan ning the transportation of frozen and chilled food products - V. E. Selyun; L. S. Trofimova (Интеллект. Инновации. Инвестиции)
The relevance of this study is substantiated by the fact that the modern transport classification of goods does not distinguish a separate group of «frozen and chilled food products, ready for consumption» taking into account the entire set of properties of such goods. The lack of scientifically based planning of the rolling stock operation taking into account the range of features of the properties of these goods, which manifest themselves during transportation from the manufacturer to the consumer, in practice leads to non-fulfillment of the requirements of the participants in the transport process. In the practice of transportation, there is an interrelationship between the participants in the transport process, taking into account the requirements of regulatory documents, the properties of the cargo. A description of the relationship between the operational indicators of the rolling stock will ensure the development of a scientifically based planning tool for fulfilling the conditions of delivery of goods to the consumer and making a profit for the carrier. The purpose of the study is to improve the transport classification of goods for planning the transportation of frozen and chilled food products taking into account the relationship of operational indicators.